Identification of the Main Problems in Using Cooperative Management in Slovak Enterprises and the Proposal of Convenient Recommendations - Vodak, Josef; Soviar, Jakub; Lendel, Viliam (Communications - Scientific Letters of the University of Zilina, 2013)
The main purpose of the article is to present some knowledge in cooperative management focused on the area of management and marketing and to show possibility to use the cooperation in a company practice effectively. The article contains drafts for successful functioning of the cooperation in practice. There are also identified the main fields of potential problems which should be discussed by responsible participants within cooperation to achieve effective functioning. The solution of the questions researched within the article needs to use several methods depending on the character of particular parts of the solution.
Keywords: cooperative management; research of cooperation potential; cooperation towards competitiveness